Drug Use and Gender in the Life Histories of young, middle class adults in Rio de Janeiro, Brazil - Silva, Patrícia Castro de Oliveira e; Souza, Cecília de Mello e; Peres, Simone Ouvinha (Saúde e Sociedade, 2021)
Drug use by young women has shown rates increasingly closer to those of men, or even higher depending on the substance. Considering the scarcity of research conducted with female drug users, especially those of higher socioeconomic status, this study focused on gender and drug use. Ethnographic research was conducted in bars and nightclubs in the southern and downtown regions of the city of Rio de Janeiro. We argue that unequal gender relations and normative models of femininity and masculinity are reproduced in the initiation and maintenance of drug use, revealing gender specificities, including the harmful health and social consequences of drug use for women. Although drug use by young adults alternates between challenging and accepting gender norms, female users are more stigmatized and socially marginalized, depend on men for access to drugs, and experience gender- based violence from their intimate partners and at drug sales points.